LEGAL REVIEW OF THE EXPANSION OF PAPUA PROVINCE INTO THREE NEW PROVINCES BASED ON LAW OF THE REPUBLIC OF INDONESIA NUMBER 21 OF 2001 CONCERNING SPECIAL AUTONOMY FOR PAPUA PROVINCE - Reyhanka Abid Putera Indrajaya; Amancik; Edra Satmaidi (Universitas Bengkulu, 2025)
In 2022, Papua Province was divided into three new provinces: South Papua, Central Papua, and Papua. This regional expansion raised legal concerns, particularly regarding unmet technical requirements and the limited consideration of the aspirations of the Papuan People’s Assembly (MRP) and the Papuan Regional House of Representatives (DRP) as representatives of indigenous Papuans. This study analyzes the legal considerations and implications of the expansion. This normative juridical research applies statutory and comparative approaches supported by literature review. Legal materials include primary legislation, secondary sources such as books and journals, and tertiary materials from online sources. The findings indicate that the government based the expansion on philosophical, sociological, and juridical considerations. Philosophically, it aimed to realize the third and fifth principles of Pancasila. Sociologically, it sought to enhance welfare, development, and security in Papua. Juridically, it referred to Article 18B of the 1945 Constitution. However, shortcomings were identified, including a rushed process, limited accommodation of local aspirations, and potential inconsistency with Article 35A of Law No. 23 of 2014. Despite these issues, the special autonomy status remains applicable to the newly established provinces.